Genetic diversity and haplotype distribution patterns analysis of cytb and RAG2 sequences in Rana hanluica from southern China - Deng, Zeshuai; Li, Yuan; Gao, Zhiwei; Zhang, Zhiqiang; Yang, Daode (Frontiers in Genetics, 2024)
Rana hanluica: an endemic amphibian of China, is found in the hills and mountains south of the Yangtze River. In this comprehensive study, we collected 162 samples from 14 different localities to delve into the genetic diversity of Rana hanluica using mitochondrial Cytb and nuclear RAG2 as genetic markers. Our findings reveal that the Nanling Mountains, specifically regions like Jiuyi Shan, Jinggang Shan, Mang Shan, and Qiyun Shan, are genetic hotspots harboring remarkable diversity. The research results also indicate that there is gene flow among the various populations of the species, and no distinct population structure has formed, which may be due to migration. Moreover, populations in some regions, as well as the overall population, show signs of a possible genetic bottleneck, which we speculate may have been caused by climate change. However, given the exploratory nature of our study, further investigations are warranted to confirm these observations. Through phylogenetic analyses, we uncovered indications that R. hanluica might have originated within the Nanling region, dispersing along the east-west mountain ranges, with a significant contribution originating from Jiuyi Shan. The genetic distributions uncovered through our research reflect historical migratory patterns, evident in the distinct haplotypes of the RAG2 gene between the western and eastern parts of the studied area. Moreover, Heng Shan and Yangming Shan exhibited unique genetic signatures, possibly influenced by geographic isolation, which has shaped their distinct genotypes. The insights gained from this study hold profound implications for conservation efforts. By identifying regions rich in genetic diversity and crucial gene flow corridors, we can develop more effective conservation strategies. Preserving these genetically diverse areas, especially within the Nanling Mountains, is vital for maintaining the evolutionary potential of R. hanluica. In conclusion, our research has laid a solid foundation for understanding the genetic landscape of R. hanluica, shedding light on its origins, population structures, and evolutionary trajectories. This knowledge will undoubtedly guide future research endeavors and inform conservation strategies for this endemic amphibian.